Impact of Mobile and Digital Health Technologies on Health Education and Disease prevention in Community Settings: A Systematic Review - Mehta, Sonia; Kumari, Bandna; Salvi, Rupali (Journal of Neonatal Surgery, 2025)
Background: Mobile and digital health technologies are increasingly being adopted in community settings to enhance health education and disease prevention, especially in low-resource environments. While the global uptake of such technologies is rising, there remains a need for consolidated evidence regarding their effectiveness in improving health outcomes at the community level. Objective: To systematically review and evaluate the effectiveness, feasibility, and health outcomes of mobile and digital health interventions aimed at health education and disease prevention in community-based settings. Methods: A systematic search was conducted across six databases (PubMed, Scopus, Web of Science, CINAHL, PsycINFO, and Embase) for studies published between January 2013 and December 2024. Inclusion criteria focused on community-based interventions using mobile or digital tools targeting health education or disease prevention. A total of six eligible studies were included, comprising randomized controlled trials, quasi-experimental studies, and cross-sectional evaluations. Data were extracted and synthesized narratively due to heterogeneity in outcome measures. Results: Across the six studies included in this review, a total of 2,247 participants were evaluated across diverse community settings. The use of mobile health (mHealth) tools demonstrated statistically significant improvements in several key health outcomes. Notably, vaccination uptake increased by 23.5% (p < 0.01), highlighting the effectiveness of mobile interventions in improving immunization rates in rural and underserved areas. In the domain of sexual health, a mobile-based educational intervention resulted in a mean score increase of 2.1 ± 0.5 in STI preventive behavior (p < 0.001), indicating a strong impact on health knowledge and behavioral change. Among hypertensive patients, the use of a mobile app for self-monitoring led to a significant reduction in systolic blood pressure, with an average decrease of 10.2 mmHg (p < 0.001), underscoring the clinical potential of digital self-management tools. Additionally, 68% of participants reported improvements in dietary and physical activity behaviors following mHealth interventions (p < 0.05), supporting the role of mobile tools in promoting healthy lifestyles. Engagement levels were also high, with more than 90% program completion rates reported in four of the six studies, suggesting strong feasibility and acceptability of these interventions. Conclusion: Mobile and digital health interventions are effective, feasible, and well-accepted tools for promoting health education and disease prevention in community settings. These technologies can significantly enhance screening coverage, health literacy, and chronic disease management. Future research should prioritize long-term evaluation, cost-effectiveness, and strategies for integrating digital tools within existing health systems, especially in underserved regions.